Trochlear dysplasia and patellar instability in patients with Down syndrome - Moreira,Tiago Amaral Rebouças (2015)
OBJECTIVE: To analyze occurrences of trochlear dysplasia in patients with Down syndrome in the presence and absence of femoropatellar instability.METHODS: Eleven knees with stable patellae and thirteen with unstable patellae in patients with Down syndrome were compared. Radiographs were produced to evaluate patellar height, trochlear angle and femoropatellar congruence angle.RESULTS: The prevalence ratio for a high patella between the unstable and the stable patients was 1.01 using the Insall-Salvati index and 0.68 using the Caton-Deschamps index. For an abnormal congruence angle, the prevalence ratio was 2.04. An increased congruence angle was only found in four cases, all presenting instability.CONCLUSIONS: Trochlear dysplasia was only found in cases of instability. The trochlear groove angle and the femoropatellar congruence angle correlated with the presence of patellar instability.